Synthesising bushmeat research effort in West and Central Africa: A new regional database. (January 2015) - Taylor, G.; Scharlemann, J.P.W.; Rowcliffe, M.; Kümpel, N.; Harfoot, M.B.J.; Fa, J.E.; Melisch, R.; Milner-Gulland, E.J.; Bhagwat, S.; Abernethy, K.A.; Ajonina, A.S.; Albrechtsen, L.; et al.
Highlights: Hunting wild animals supports human livelihoods, but is also a threat to animal conservation. We created a database for bushmeat offtake, consumption and trade in West and Central Africa. We collated data on 177 species from 275 sites across 11 countries collected over 30 years. The database enables analyses of spatial and temporal patterns, and of drivers of bushmeat harvesting. Knowledge gaps and future research priorities for bushmeat harvesting can be identified using the database. Abstract: Unsustainable hunting threatens both biodiversity and local livelihoods. Despite high levels of research effort focused on understanding the dynamics of bushmeat trade and consumption, current research is largely site specific. Without synthesis and quantitative analysis of available case studies, the national and regional characteristics of bushmeat trade and consumption remain largely speculative, impeding efforts to inform national and regional policy on bushmeat trade. Here we describe the structure and content of the West and Central African bushmeat database which holds quantitative data on bushmeat sales, consumption and offtake for 177 species from 275 sites across 11 countries in two regions, spanning three decades of research. Despite this wealth of available data, we found important biases in research effort. The majority of studies in West and Central Africa have collected market data, which although providing a useful record of bushmeat sales, are limited in their ability to track changes in hunting offtake. In addition, few data exist for West Africa, and few studies have tracked changes over time, using repeat sampling. With new initiatives in the regions to track bushmeat hunting, this database represents an opportunity to synthesise current and future data on bushmeat hunting, consumption and trade in West and Central Africa, identify gaps in current understanding, and systematically target future monitoring efforts.